Triphala herbal extract suppresses inflammatory responses in LPS-stimulated RAW 264.7 macrophages and adjuvant-induced arthritic rats via inhibition of NF-κB pathway. (3rd July 2016) - Kalaiselvan, Sowmiya; Rasool, Mahaboob Khan
Abstract: This study sought to explore the mechanism of anti-inflammatory effect of triphala in lipopolysaccharide (LPS)-stimulated RAW 264.7 macrophages and in adjuvant-induced arthritic rats. In stimulated RAW 264.7 cells, triphala (100–300 μg/ml) significantly suppressed production of inflammatory mediators (e.g. TNF α, IL-1 β, IL-6, MCP-1, VEGF, NO, PGE2 ), intracellular free radicals and release of lysosomal enzymes (e.g. acid phosphatase, β -galactosidase, N -acetyl glucosamindase and cathepsin D) in a dose-related manner. With triphala, mRNA levels of genes for pro-inflammatory TNFα, IL-1β, IL-6 and MCP-1, inflammatory iNOS and COX-2 enzymes and NF-κBp65 were down-regulated in the stimulated cells; in contrast, there was up-regulation of heme oxygenase-1 (HO-1) expression. Western blot analyses revealed that triphala suppressed the protein expression of NF- κ B p65 and p-NF- κ B p65 in the stimulated cells, which subsequently reduced over-expression of TNF α, IL-17, iNOS and COX-2 in a manner similar to that observed with BAY 11-7082, an I κ B kinase inhibitor. Immunofluorescence analysis revealed inhibition of p-NF- κ B p65 nuclear translocation and COX-2 protein expression caused by triphala. Consistent with these findings, the animal studies presented confirmed that triphala exhibited anti-inflammatory effects in a rat adjuvant-induced arthritis model by reducing of inflammatory mediator (e.g. IL-17, COX-2 and RANKL) expression via inhibition of NF- κ B activation. Taken together, the results here demonstrated that triphala has potential anti-inflammatory applications that could be used for the treatment of inflammatory disorders, including rheumatoid arthritis.